Arabidopsis Sucrose Transporter AtSuc1 introns act as strong enhancers of expression. (12th March 2020) - Lasin, Praphapan; Weise, Andreas; Reinders, Anke; Ward, John M
Abstract: The expression of AtSUC1 is controlled by the promoter and intragenic sequences. AtSUC1 is expressed in roots, pollen and trichomes. However, AtSUC1 promoter- GUS transgenics only show expression in trichomes and pollen. Here, we show that the root expression of AtSUC1 is controlled by an interaction between the AtSUC1 promoter and two short introns. The deletion of either intron from whole-gene- GUS constructs results in no root expression, showing that both introns are required. The two introns in tandem, fused to GUS, produce high constitutive expression throughout the vegetative parts of the plant. When combined with the promoter, the expression driven by the introns is reduced and localized to the roots. In Arabidopsis seedlings, exogenously applied sucrose induces the expression of AtSUC1 in roots and causes anthocyanin accumulation. atsuc1 loss-of-function mutants are defective in sucrose-induced anthocyanin accumulation. We show that an AtSUC1 whole-gene- GUS construct expressing a nonfunctional AtSUC1 (D152N) mutant, that is transport inactive, is defective in sucrose-induced AtSUC1 expression when expressed in an atsuc1 -null background. We also show that the transport-defective allele does not complement the loss of sucrose-induced anthocyanin accumulation in null atsuc1 mutants. The results indicate that sucrose uptake via AtSUC1 is required for sucrose-induced AtSUC1 expression and sucrose-induced anthocyanin accumulation and that the site for sucrose detection is intracellular.